The origins of the first world war - Mulligan, William, 1975- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2017)
The second edition of this leading introduction to the origins of the First World War. Updated to take account of the latest debates around the war's origins and outbreak, this is an essential classroom text which significantly revises our understanding of diplomacy, political culture, and economic history from 1870 to 1914.
Security and expansion : the great powers and geopolitics, 1871-1914 -- The military, war, and international politics -- Public opinion and international relations -- The world economy and international politics before 1914 -- The July crisis -- Conclusion.
Includes bibliographical references (pages 239-253) and index.
ENH
Trim Education
Keywords: 1914-1918; World War, 1914-1918 -- Causes; World War, 1914-1918 -- Causes; War -- Causes; Vorgeschichte; English language; Första världskriget 1914-1918.; Europa